2012
DOI: 10.1177/0961203312468624
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cyclophosphamide on menstruation and pregnancy in women with rheumatologic disease

Abstract: In this cohort of young women with rheumatologic disease, more women with prior CYC than without had amenorrhea, nulliparity, and infertility. GnRH-a co-therapy may prevent these adverse effects of CYC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 17 publications
2
49
0
7
Order By: Relevance
“…Studies have reported ovarian insufficiency in 10-83 % of female SLE patients treated with CYC, depending primarily on the subject's age at initiation of treatment and cumulative CYC dose [25][26][27]. Medeiros et al showed that SLE patients treated with a cumulative CYC dose of greater than 10 g had a 3.2 times higher risk of developing ovarian insufficiency than patients receiving a cumulative dose lower than 10 g [28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported ovarian insufficiency in 10-83 % of female SLE patients treated with CYC, depending primarily on the subject's age at initiation of treatment and cumulative CYC dose [25][26][27]. Medeiros et al showed that SLE patients treated with a cumulative CYC dose of greater than 10 g had a 3.2 times higher risk of developing ovarian insufficiency than patients receiving a cumulative dose lower than 10 g [28].…”
Section: Discussionmentioning
confidence: 99%
“…In their series, even though women with prior cyclophosphamide exposure were 4 years younger at diganosis than those without cyclophosphamide, 30.4% of them had cessation of menses compared to 0% of those without cyclophosphamide (p<0.05). Of the women with prior cyclophosphamide exposure those with loss of menses were older at study enrollment, older at cyclophosphamide treatment and higher cumulative doses of cyclophosphamide than those who retained menstrual function [18]. AMH appear to be a reliable indicator of residual ovarian reserve postexposure to cyclophosphamide based on the accumulating evidence of the aforementioned studies.…”
Section: The Impact Of Cytotoxic Immunosuppressive Therapies On Ovarimentioning
confidence: 99%
“…• Chronic inflammatory state may prevent the proper functioning of the hypothalamic-pituitary-ovarian axis (HPO) [15] • Autoimmune ovarian injury most commonly in the form of autoimmune oophoritis may hamper ovarian function [16] • Lupus flares are associated with hyperprolactinemia, which may interfere with ovulation process and affect immune activity [17] • Thrombocytopenia, antiphospholipid antibodies, and the use of glucocorticoids and/or nonsteroidal anti-inflammatory drugs can contribute to menorrhagia [14] • Temporary or even permanent early (or premature) amenorrhea may result from autoimmune ovarian injury or from the administration of cytotoxic agents such as cyclophosphamide [18] Figure 1: Contributory factors causing menstrual irregularity, ovarian failure and infertility in women with systemic lupus erythematosus. SLE involves many organ systems.…”
Section: Adverse Reproductive Outcomes In Women With Systemic Lupus Ementioning
confidence: 99%
See 1 more Smart Citation
“…Золотым стандартом поликом-понентной терапии активной СКВ является комбинация вы-С О В P E М Е Н Н А Я Р Е В М А Т О Л О Г И Я № 1 ' 1 6 О Б З О Р Ы соких доз ГК и ЦФ. Однако и ЦФ вносит существенную леп-ту в развитие органных поражений, вызывая аменорею, бес-плодие и повышая риск развития опухолей [55]. Есть надеж-да, что появление генно-инженерных биологических препа-ратов (белимумаб, ритуксимаб, эпратузумаб), применение которых не ассоциируется с развитием «традиционных» ор-ганных повреждений, сделает терапию СКВ не только более эффективной, но и более безопасной [56].…”
Section: циклофосфамидunclassified